2008
DOI: 10.1590/s0004-28032008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Transplante hepático: repercussões na capacidade pulmonar, condição funcional e qualidade de vida

Abstract: e Mariane Borba MONTEIRO 2,3 RESUMO -Racional -O transplante hepático é utilizado para o tratamento de doenças hepáticas em estado avançado, quando a sobrevida e a função hepática são aumentadas após o procedimento. Objetivo -Avaliar e comparar a função pulmonar, a condição funcional e a qualidade de vida de pacientes candidatos ao transplante hepático e após a realização do procedimento cirúrgico no período de 1, 3, 6, 9 e 12 meses de pós-operatório. Métodos -Trabalho transversal, observacional, com amostra d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
(21 reference statements)
0
8
0
11
Order By: Relevance
“…Acredita-se que essa percepção de limitação funcional possa ter sido o fator chave para que houvesse uma resposta negativa quanto aos domínios de função emocional e preocupação. Barcelos et al 15 avaliaram a QV e a condição funcional dos pacientes pré-transplante e naqueles submetidos à alocação do enxerto. Os do pré-transplante apresentaram diminuição nos domínios capacidade funcional e saúde mental do questionário de qualidade de vida SF-36, quando comparados com os do pós-transplante.…”
Section: Discussionunclassified
“…Acredita-se que essa percepção de limitação funcional possa ter sido o fator chave para que houvesse uma resposta negativa quanto aos domínios de função emocional e preocupação. Barcelos et al 15 avaliaram a QV e a condição funcional dos pacientes pré-transplante e naqueles submetidos à alocação do enxerto. Os do pré-transplante apresentaram diminuição nos domínios capacidade funcional e saúde mental do questionário de qualidade de vida SF-36, quando comparados com os do pós-transplante.…”
Section: Discussionunclassified
“…Barcelos et al (1) evaluated the quality of life in patients before transplantation and found a reduction in the scores of the SF-36 compared with subjects who underwent liver transplantation. Our findings demonstrate that individuals who wait in the waiting list for allocation of grafts have reduced the scores of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The association of all these factors causes negative influence in the activities of daily living (ADL) and in the quality of life of this population (5)(6)(7) . In a previous study carried out by our group, alterations in the frequency and severity of hepatic diseases, as well as in the functionality and quality of life of the individuals with severe hepatic disease and who are on the waiting list for an hepatic transplant was found (LTx) (8) . Due to the increase in the number of candidates to LTx, classification models with several clinical variables were created to determine the severity of the hepatic disease.…”
Section: Introductionmentioning
confidence: 94%